Outcome of gastric cancer in the elderly: a population-based evaluation of the Munich cancer registry - Schlesinger-Raab, Anne; Mihaljevic, André Leopold; Egert, Silvia; Emeny, Rebecca; Jauch, Karl-Walter; Kleeff, Jörg; Novotny, Alexander; Nüssler, Natascha C.; Rottmann, Miriam; Schepp, Wolfgang; Schmitt, Wolfgang; Schubert-Fritschle, Gabriele; et al. (Gastric cancer, 2016)
Gastric cancer, Stomach cancer, Elderly, Cancer registry, Comparative effectiveness research